Gut Microbiota and Subclinical Cardiovascular Disease in Patients with Type 2 Diabetes Mellitus - Tsai, Hui-Ju; Tsai, Wei-Chung; Hung, Wei-Chun; Hung, Wei-Wen; Chang, Chen-Chia; Dai, Chia-Yen; Tsai, Yi-Chun (Nutrients, 2021)
Type 2 diabetes (T2D) is associated with an increased risk of cardiovascular disease (CVD). The gut microbiota may contribute to the onset and progression of T2D and CVD. The aim of this study was to evaluate the relationship between the gut microbiota and subclinical CVD in T2D patients. This cross-sectional study used echocardiographic data to evaluate the cardiac structure and function in T2D patients. We used a quantitative polymerase chain reaction to measure the abundances of targeted fecal bacterial species that have been associated with T2D, including Bacteroidetes, Firmicutes, Clostridium leptum group, Faecalibacterium prausnitzii, Bacteroides, Bifidobacterium, Akkermansia muciniphila, and Escherichia coli. A total of 155 subjects were enrolled (mean age 62.9 ± 10.1 years; 57.4% male and 42.6% female). Phyla Bacteroidetes and Firmicutes and genera Bacteroides were positively correlated with the left ventricular ejection fraction. Low levels of phylum Firmicutes were associated with an increased risk of left ventricular hypertrophy. High levels of both phylum Bacteroidetes and genera Bacteroides were negatively associated with diastolic dysfunction. A high phylum Firmicutes/Bacteroidetes (F/B) ratio and low level of genera Bacteroides were correlated with an increased left atrial diameter. Phyla Firmicutes and Bacteroidetes, the F/B ratio, and the genera Bacteroides were associated with variations in the cardiac structure and systolic and diastolic dysfunction in T2D patients. These findings suggest that changes in the gut microbiome may be the potential marker of the development of subclinical CVD in T2D patients.